Pelletization of composted swine manure solid fraction with different organic co-formulates: effect of pellet physical properties on rotating spreader distribution patterns - Elio Romano; Massimo Brambilla; Carlo Bisaglia; Niccolò Pampuro; Ester Foppa Pedretti; Eugenio Cavallo (International Journal of Recycling of Organic Waste in Agriculture)
Introduction In Europe, because of the high production levels of livestock farming in general and pig farming in particular, animal waste management has become increasingly important to comply with the required lowering of livestock farming environmental pressure. Usually manures undergo solid/liquid separation, which generates one clarified liquid fraction and one nutrient-rich solid fraction suitable for in farm composting (both raw and in mixture with other bulking agents). This can be used to produce soil amendments, whose management can be further improved by pelletization that, against technological and environmental advantages, has the disadvantage of requiring a quite high energy input. Results Four different pelleted organic fertilizer formulations made of swine manure solid fraction (SMSF) composted both by itself and with sawdust (SMSF-SD), wood chips (SMSF-WC) and wheat straw were tested to highlight differences in physico-chemical and land distribution features. They were compared with two pelleted organic fertilizers ordinarily available at retailers. Results show that, as far as physical and chemical features are concerned, the greatest difference from the reference products used in this study is found in pellet size distribution after spreading since the disintegrating action of the rotating vanes does not affect the tested formulation with the same intensity as the commercial products. Distribution tests showed that SMSF-SD was the formulation with better longitudinal and transverse distribution, while SMSF was the one showing good transverse but poor longitudinal distribution. Conclusions In farm pelletizing of SMSF composted with different organic waste materials as co-formulates can turn into organic fertilizer formulations comparable with pelleted organic fertilizers ordinarily available at retailers. SMSF-WC was the formulation with the best resistance to fragmentation induced by spreader vanes. SMSF-SD was the formulation showing better longitudinal and transverse distribution, while SMSF showed good transverse but poor longitudinal distribution. These promising results enhance the importance of co-composting as a way to increase livestock farming sustainability and produce better manure compost for wider agricultural uses.